3D Bioprinting: Fast Stereolithography Printing of Large‐Scale Biocompatible Hydrogel Models (Adv. Healthcare Mater. 10/2021). Issue 10 (19th May 2021) - Anandakrishnan, Nanditha; Ye, Hang; Guo, Zipeng; Chen, Zhaowei; Mentkowski, Kyle I.; Lang, Jennifer K.; Rajabian, Nika; Andreadis, Stelios T.; Ma, Zhen; Spernyak, Joseph A.; Lovell, Jonathan F.; Wang, Depeng; et al.
Abstract : In article number 2002103, Ruogang Zhao, Chi Zhou, and co‐workers, present the development of fast hydrogel stereolithography technology (FLOAT) for the fabrication of large‐sized biocompatible hydrogel models. The high printing speed of the FLOAT significantly reduces environmental stress‐induced cellular injuries. The perfusable vessel networks enabled by the multiscale printing capability allows maintenance of high cellular viability and metabolic functions in the core of the large‐sized models.